Nepal Country Report on Biological Diversity Kathmandu: The World Conservation Union 1999, Shrestha Tirtha Bahadur - Poudel, P. C. (Himalayan Review, 2011)
Not available (Book Review) Key words: Biological diversity The Himalayan Review Nepal Geographical Society Vol. XXXII 2001 Page: 59-60 Uploaded date: 7 June, 2011